Structure-odor relationships of linalool, linalyl acetate and their corresponding oxygenated derivatives - Elsharif, Shaimaa A.; Banerjee, Ashutosh; Buettner, Andrea (Frontiers in Chemistry, 2015)
Linalool 1 is an odorant that is commonly perceived as having a pleasant odor, but is also known to elicit physiological effects such as inducing calmness and enhancing sleep. However, no comprehensive studies are at hand to show which structural features are responsible for these prominent effects. Therefore, a total of six oxygenated derivatives were synthesized from both 1 and linalyl acetate 2, and were tested for their odor qualities and relative odor thresholds (OTs) in air. Linalool was found to be the most potent odorant among the investigated compounds, with an average OT of 3.2 ng/L, while the 8-hydroxylinalool derivative was the least odorous compound with an OT of 160 ng/L; 8-carboxylinalool was found to be odorless. The odorant 8-oxolinalyl acetate, which has very similar odor properties to linalool, was the most potent odorant besides linalool, exhibiting an OT of 5.9 ng/L. By comparison, 8-carboxylinalyl acetate had a similar OT (6.1 ng/L) as its corresponding 8-oxo derivative but exhibited divergent odor properties (fatty, greasy, musty). Overall, oxygenation on carbon 8 had a substantial effect on the aroma profiles of structural derivatives of linalool and linalyl acetate.